The Economic Impact of the Great Recession on Aboriginal People Living off Reserve in Canada - Lamb, Danielle (Relations industrielles / Industrial Relations, 2015)
SummaryThe present analysis seeks to examine whether the 2008 recession had a differential impact on Aboriginal as compared to non-Aboriginal Canadians as measured by the differences in the probability of unemployment between the two groups. Specifically, the present study tests two hypotheses: 1- Aboriginal people have been disproportionately burdened by the Great Recession as compared to non-Aboriginal people, and as a consequence; 2- Aboriginal people are more likely than non-Aboriginal people to be discouraged workers.The study uses data obtained from the master files of the Canadian Labour Force Survey for the years 2007 to 2012 inclusive to estimate the probability that an individual is unemployed based on a set of observable characteristics for a sample of labour force participants. The methodology begins by estimating a pooled model across all years, which includes controls for Aboriginal identity. Secondly, individual models of the probability of unemployment are estimated for each year for Aboriginal and non-Aboriginal labour force participants. The difference in the probability of unemployment from pooled models estimated separately for Aboriginal and non-Aboriginal peoples are decomposed to reveal the proportion of the gap that is due to differences in observable characteristics between the two groups and the amount of the gap that is attributable to differential returns to those characteristics. To investigate the second hypothesis, the study estimates the probability that a respondent is a discouraged worker based on the entire sample of both economically active and inactive persons (i.e. labour force participants and well as those not in the labour force).The results of both the pooled and individual models of the probability of unemployment support the first hypothesis, that Aboriginal peoples were disproportionately burdened by the 2008 recession as seen in higher and more enduring probabilities of unemployment. By the 2012, estimated unemployment rates had roughly returned to their pre-recessionary levels for Aboriginal and non-Aboriginal respondents with strongest labour force attachments. When individuals with weaker labour force attachments (i.e. those who have been unemployed for more than twelve months) are included in the analysis, the gap between the probability of unemployment for Aboriginal and non-Aboriginal persons widens. Furthermore, the second hypothesis, that Aboriginal people are more likely to be discouraged workers, was supported, as Aboriginal people were more likely to be discouraged workers in 2008-2010 and 2012.